2020
DOI: 10.3390/app10238537
|View full text |Cite
|
Sign up to set email alerts
|

Linear System Identification and Vibration Control of End-Effector for Industrial Robots

Abstract: This paper presents the discrete state space mathematical model of the end-effector in industrial robots and designs the linear-quadratic-Gaussian controller, called LQG controller for short, to solve the low frequency vibration problem. Though simplifying the end-effector as the cantilever beam, this paper uses the subspace identification method to determine the output dynamic response data and establishes the state space model. Experimentally comparing the influences of different input excitation signals, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The chirp or swept sinusoidal signals are widely used in applications like synthetic sounds, mechanical vibration [60], radar and system identification [61,62]. Consider the overall transfer function of the parallel connection of 𝑚 transfer functions given as (15) where 𝛾 𝑓 𝑖 ∈ R is the gain that reflects the importance of the excitation band associated with the frequency 𝜔 𝑠 𝑖 , and 𝜃 𝑠 𝑖 ∈ [−𝜋, 𝜋] is its associated shift angle.…”
Section: Excitation Chirps Signalsmentioning
confidence: 99%
“…The chirp or swept sinusoidal signals are widely used in applications like synthetic sounds, mechanical vibration [60], radar and system identification [61,62]. Consider the overall transfer function of the parallel connection of 𝑚 transfer functions given as (15) where 𝛾 𝑓 𝑖 ∈ R is the gain that reflects the importance of the excitation band associated with the frequency 𝜔 𝑠 𝑖 , and 𝜃 𝑠 𝑖 ∈ [−𝜋, 𝜋] is its associated shift angle.…”
Section: Excitation Chirps Signalsmentioning
confidence: 99%
“…We chose to focus on second-order sensors in this paper because a significant proportion of real sensors are defined by this dynamic order, such as vibration and pressure sensors [28][29][30][31][32], and the mechanical construction of a wide variety of other measurement instruments [33]. The proposed procedure can be applied in both the time and frequency domains [34][35][36], which are used in practical implementations of procedures intended for sensor modelling. The solutions proposed in this study consists of three main steps:…”
Section: Introductionmentioning
confidence: 99%
“…where f r denotes the resonant frequency [Hz] [35,36]. Equations ( 7) and ( 8) form the basis for applying the MC method in the frequency domain.…”
mentioning
confidence: 99%
“…A method to identify a nonlinear system [6] and proper model selection procedure was also suggested [7]. A vibration of the end-effector for industrial robots was recently identified through a linear system identification method; after that, a vibration was reduced with the linear quadratic-Gaussian controller [8]. Moreover, an active vibration isolation system was presented for vibration isolation of a surveillance system [9].…”
Section: Introductionmentioning
confidence: 99%